The Mitigation of CO2 Emissions in the Sea Water Desalination Plant with Reverse Electrodialysis Power Generation - Handaja, Suka; Susanto, Heru; Hermawan (Indonesian Journal of Energy and Mineral, 2021)
Climate change is a major issue that is very interesting to discuss. Climate change is believed to be caused by the greenhouse gas effect. CO2 is one of the gases that causes the greenhouse gas effect. Therefore, to avoid the dangers of climate change, reducing CO2 emissions is the main topic in various articles. In this article, CO2 emission mitigation is analyzed in the sea water desalination plant using reverse electrodialysis power generation. Reverse electrodialysis is a power plant that does not produce CO2 emissions which converts energy from the difference in salinity of two solutions into electrical energy through selective ion membrane technology. There are 8 sea water desalination (SWD) unit which produces 242 tons/h of clean water for industrial activity and blowdown water of 3,161 tons/h, the blowdown water is wastewater. The SWD unit requires 3.043 tons/h of seawater as feed water, 0.164 MW of electricity and 86 tons/h of steam worth 64.1 MW as an energy. The energy are met from the combined heat and power operation. Combined heat and power require of fuel oil and fuel gas which produce CO2 emissions of 1,352,445,626 kgCO2/y. From the analysis on the SWD plant, the CO2 emission is 148,411,874 kgCO2/y. By implementing reverse electrodialysis power generation, blowdown water at the SWD plant which has a salinity concentration of 680 mol/m3 can produce electricity of 0.414 MW (3,636 MWh/y). If the electricity generated is used to substitute the electricity needs at the refinery plant, the CO2 emissions that can be mitigated is 2,955,915 kgCO2/y